2020
DOI: 10.1111/iju.14172
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of postoperative delirium in elderly patients undergoing urological surgery: A multi‐institutional prospective study

Abstract: Objectives To investigate the incidence and risk factors of postoperative delirium among patients aged ≥65 years undergoing elective urological surgery. Methods From April 2015 through December 2016, 1023 consecutive patients aged ≥65 years who received transurethral, laparoscopic (with or without robot assistance) or open surgery in eight institutions were enrolled in this prospective observational study. Their preoperative cognitive status was assessed with the Hasegawa Dementia Scale‐Revised score. The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
2
38
1
1
Order By: Relevance
“…This findings supported by Ozbas et al, (2018), which shows a higher rate of incidence in elderly participants undergoing spinal anesthesia in hip surgery. Other study done in urological surgery, found a definite correlation with the incidence of POD (Matsuki, et al, 2017).…”
Section: Discussionmentioning
confidence: 59%
“…This findings supported by Ozbas et al, (2018), which shows a higher rate of incidence in elderly participants undergoing spinal anesthesia in hip surgery. Other study done in urological surgery, found a definite correlation with the incidence of POD (Matsuki, et al, 2017).…”
Section: Discussionmentioning
confidence: 59%
“…Although promising, these results do have limitations and therefore the CDT would need extensive further evaluation before use as a screening tool within clinical practice. A recently published prospective study of over 1000 patients identified a different cognitive screening tool for dementia was associated with development of POD [42]. The authors found that a Hasegawa Dementia Scale-Revised (HDS-R) score of less than 20 was an independent risk factors for POD in elderly urological patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…investigated the incidence and risk factors of postoperative delirium among patients aged ≥65 years undergoing elective urological surgery. They concluded that the incidence was just 3.4%, and preoperative history of cerebrovascular disease, cognitive status, low serum albumin level and operative duration was associated with the development of postoperative delirium . The incidence rates of delirium were significantly higher for laparoscopic/open surgery (18/328, 5.5%) than that for transurethral surgery (14/618, 2.3%, P = 0.015).…”
mentioning
confidence: 99%
“…Although the optimal assessment tool for delirium requires further investigation, their findings showed that the Intensive Care Delirium Screening Checklist is a useful tool for assessment of delirium. Also, they developed a screening flow model for risk stratification, and suggested the risk for postoperative delirium was <5%, 5–15% and >25% in the low‐, intermediate‐ and high‐risk patients, respectively . A validation study for this model is necessary.…”
mentioning
confidence: 99%